Therapeutic Effects of Licorice and Dried Ginger Decoction on Activity-Based Anorexia in BALB/c AnNCrl Mice - Kim, Do-Hyun; Kim, Joong Sun; Kim, Jeongsang; Jeong, Jong-Kil; Son, Hong-Seok; Park, Seong-Eun; Jo, Jeakwon; Ryu, Seung Mok; Kim, Eun-San; Lee, Sung-Jun; Lee, Soong-In (Frontiers in Pharmacology, 2020)
Licorice and dried ginger decoction (Gancao-ganjiang-tang, LGD) is used for nausea and anorexia, accompanied by excessive sweating in Traditional Chinese Medicine. Herein, we investigated the therapeutic effects of LGD using the activity-based anorexia (ABA) in a mouse model. Six-week-old female BALB/c AnNCrl mice were orally administered LGD, water, licorice decoction, dried ginger decoction, or chronic olanzapine, and their survival, body weight, food intake, and wheel activity were compared in ABA. Additionally, dopamine concentration in brain tissues was evaluated. LGD significantly reduced the number of ABA mice reaching the drop-out criterion of fatal body weight loss. However, LGD showed no significant effects on food intake and wheel activity. We found that in the LGD group the rise of the light phase activity rate (LPAR) inhibited body weight loss. Licorice or dried ginger alone did not improve survival rates, they only showed longer survival periods than chronic olanzapine when combined. In addition, LGD increased the dopamine concentration in the brain. The results from the present study showed that LGD improves the survival of ABA mice and its mechanism of action might be related to the alteration of dopamine concentration in the brain.